Short‐term outcomes of local infiltration anaesthetic in total knee arthroplasty: a randomized controlled double‐blinded controlled trial. Issue 3 (3rd December 2015) - Mulford, Jonathan S.; Watson, Anna; Broe, David; Solomon, Michael; Loefler, Andreas; Harris, Ian
Abstract: Background: The primary objective of the study was to determine if local infiltration anaesthetic (LIA) reduced total length of hospital stay in total knee arthroplasty (TKA) patients. The study also examined whether LIA improves early pain management, patient satisfaction and range of motion in TKA patients. Methods: We conducted a randomized controlled double‐blinded study. Fifty patients undergoing TKA were randomized to receive either placebo or LIA at the time of surgery and on the first day post‐operatively. Pain scores, level of satisfaction and range of motion were recorded preoperatively and post‐operatively. Results: There was no statistical difference between the groups for length of stay, post‐operative pain scores, satisfaction scores or range of motion 6 weeks post‐operatively. Conclusion: This randomized double‐blinded trial did not demonstrate a decrease in pain or reduction of length of stay due to local infiltration analgesia.